(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
Poetry translation is one of the complex types of literary translation due to being an artistic unity consisting of not only words, but also their rhythm, tone, musicality, rhyme and layers of meaning.The process of re-creating artistic transfers (metaphor, metonymy, synecdoche, etc.) in poetic translation in parallel corpus of the Uzbek language into other a foreign language always poses a number of challenges. Our thesis deals with semantic analysis the complications of re-creating artistic transfers in translation of parallel corpus.